2015
DOI: 10.1016/j.nuclphysb.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Minimal unitary representation of 5d superconformal algebra F(4) and AdS6

Abstract: We study the minimal unitary representation (minrep) of SO(5, 2), obtained by quantization of its geometric quasiconformal action, its deformations and supersymmetric extensions. The minrep of SO(5, 2) describes a massless conformal scalar field in five dimensions and admits a unique "deformation" which describes a massless conformal spinor. Scalar and spinor minreps of SO(5, 2) are the 5d analogs of Dirac's singletons of SO(3, 2). We then construct the minimal unitary representation of the unique 5d superconf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…More recent work has shown that Rac's, which are singletons of SO(d, 2) for odd d and scalar doubletons of SO(d, 2) for even d, are simply the minimal unitary representations of SO(d, 2). For odd d they admit a single deformation (spinor singleton), Di, and for even d they admit an infinite family of deformations (doubletons) [8,[24][25][26]. Furthermore there exists a one-to-one correspondence between the minimal unitary representations of SO(d, 2) and their deformations and massless conformal fields in d dimensional Minkowskian spacetimes [8].…”
Section: Higher-spin Theoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…More recent work has shown that Rac's, which are singletons of SO(d, 2) for odd d and scalar doubletons of SO(d, 2) for even d, are simply the minimal unitary representations of SO(d, 2). For odd d they admit a single deformation (spinor singleton), Di, and for even d they admit an infinite family of deformations (doubletons) [8,[24][25][26]. Furthermore there exists a one-to-one correspondence between the minimal unitary representations of SO(d, 2) and their deformations and massless conformal fields in d dimensional Minkowskian spacetimes [8].…”
Section: Higher-spin Theoriesmentioning
confidence: 99%
“…The Hilbert space of the minimal unitary representation of SO(d, 2) obtained via the quasiconformal method is spanned by states in the tensor product of the Fock space of (d − 2) bosonic oscillators with the state space of the Calogero Hamiltonian or of conformal quantum mechanics [8,39,86]. The explicit expressions for minimal unitary realization (minrep) of SO(5, 2) were given in [26]. To show that the minrep of SO(5, 2) is a positive energy unitary representation that describes a massless conformal scalar field in 5d one uses the compact 3-grading of SO(5, 2) with respect to the Lie algebra of its maximal compact subgroup SO(5) × SO(2) whose covering group is Spin(5) × U(1) ≡ USp(4) × U(1):…”
Section: Minimal Unitary Representation Of So(5 2) and Its Unique Dementioning
confidence: 99%
See 2 more Smart Citations
“…7 In dimensions 3, 4 and 6, the higher symmetries of super-Laplacians were studied in [56], thereby extending Eastwood's approach to the supersymmetric case. 8 See also [26,39,[58][59][60] for the quasiconformal approach to higher-spin (super)algebras.…”
Section: Type Abmentioning
confidence: 99%